Prevalence and co-infection with tick-borne Anaplasma phagocytophilum and Babesia spp. in red deer (Cervus elaphus) and roe deer (Capreolus capreolus) in Southern Norway. (April 2019) - Razanske, Irma; Rosef, Olav; Radzijevskaja, Jana; Bratchikov, Maksim; Griciuviene, Loreta; Paulauskas, Algimantas
Abstract: Anaplasma phagocytophilum and Babesia spp. are causative agents of tick-borne infections that are increasingly considered as a threat to animal and public health. To assess the role of cervids in the maintenance of zoonotic pathogens in Norway, we investigated the prevalence of A. phagocytophilum and Babesia spp. in free-ranging roe deer and red deer. Initial screening of spleen samples of 104 animals by multiplex real-time PCR targeting the major surface protein ( msp 2) gene and 18S rRNA revealed the presence of A. phagocytophilum infection in 81.1% red deer ( Cervus elaphus ) and 88.1% roe deer ( Capreolus capreolus ), and Babesia spp. parasites in 64.9% red deer and 83.6% roe deer, respectively. Co-infections were found in 62.2% red deer and 79.9% roe deer. Nested PCR and sequence analysis of partial msp 4 and 18S rRNA genes were performed for molecular characterization of A. phagocytophilum strains and Babesia species. A total of eleven A. phagocytophilum msp4 gene sequence variants were identified: five different variants were 100% identical to corresponding A. phagocytophilum sequences deposited in the GenBank database, while other six sequence variants had unique nucleotide polymorphisms. Sequence analysis of the 18S rRNA gene demonstrated the presence of multiple Babesia species, including Babesia capreoli, Babesia divergens, Babesia venatorum and Babesia odocoilei/Babesia cf. odocoilei . This study is the first report demonstrating the prevalence and molecular characterization of A. phagocytophilum strains and Babesia species in roe deer and red deer in Norway. The high infection and co-infection rates with A. phagocytophilum and Babesia spp. in red deer and roe deer suggest that these cervids may play an important role in the transmission of single and multiple pathogens. Graphical abstract: Image 1 Highlights: Sequences of the partial msp4 gene of A. phagocytophilum revealed 6 new variants. Babesia capreoli and B. venatorum were found only in roe deer. Babesia cf. odocoilei and B. divergens were found only in red deer. Co-infections of A. phagocytophilum and Babesia spp. were detected in both species.